Combining ability for high temperature tolerance and yield contributing traits in bread wheat - Singh, Khajan; Sharma, Satya Narayan; Sharma, Yogendra; Tyagi, Bhudeva Singh (Journal of Cereal Research, 2012)
Combining ability analysis for high temperature tolerance in bread wheat (Triticum aestivum L. Em. Thell.) involving ten diverse parents and their 45 F1 and F2 progenies indicated significant differences among the parents for gca and crosses that of sca for all the characters studied. The gca and sca components of variance were significant for all the traits. The gca/sca variance ratio below unity in both the generations showed the preponderance of non-additive gene effects for all the characters. Based on general combining ability (gca) effects and per se< performance, parents WH 789 and HD 2881 emerged as good general combiners for grain yield per plant and average to high combiners for most of the yield component characters in case of very late sown condition, it means, these genotypes probably possessed the desirable genes for high temperature tolerance during grain filling period. These genotype possessed desirable GCA effects for biological yield per plant, number of grains per spike, 1000 - grain weight, peduncle length, tillers per plant, days to heading and harvest index. On the basis of per se performance and SCA effects the crosses for grain yield were UP 2614 x HD 2851, WH 789 x PBW 520, HUW 468 x UP 2614 and HUW 468 x PBW 520 which emerged as good specific cross combinations. These crosses were the product of good x good, good x poor or poor x poor general combiners. Hybridization systems, such as multiple crossing and bi-parental mating could be useful in the genetic improvement for further amelioration of grain yield per plant in bread wheat.